Systematic review of approaches to using patient experience data for quality improvement in healthcare settings. Issue 8 (16th August 2016) - Gleeson, Helen; Calderon, Ana; Swami, Viren; Deighton, Jessica; Wolpert, Miranda; Edbrooke-Childs, Julian
Abstract : Objectives: Explore how patient-reported experience measures (PREMs) are collected, communicated and used to inform quality improvement (QI) across healthcare settings. Design: Systematic review. Setting: Various primary and secondary care settings, including general practice, and acute and chronic care hospitals. Participants: A full range of patient populations from (children through to the elderly) and staff (from healthcare practitioners to senior managers). Methods: Scientific databases were searched (CINAHL, PsycINFO, MEDLINE and Cochrane Libraries) as was grey literature. Qualitative and quantitative studies describing collection of PREM data and subsequent QI actions in any healthcare setting were included. Risk of bias was assessed using established criteria. Of 5312 initial hits, 32 full texts were screened, and 11 were included. Results: Patient experience data were most commonly collected through surveys and used to identify small areas of incremental change to services that do not require a change to clinician behaviour (eg, changes to admission processes and producing educational materials). While staff in most studies reported having made effective improvements, authors struggled to identify what those changes were or the impact they had. Conclusions: Findings suggest there is no single best way to collect or use PREM data for QI, but they do suggest some key points to consider when planning such an approach. For instance, formal training is recommended, as a lack of expertise in QI and confidence in interpreting patient experience data effectively may continue to be a barrier to a successful shift towards a more patient-centred healthcare service. In the context of QI, more attention is required on how patient experience data will be used to inform changes to practice and, in turn, measure any impact these changes may have on patient experience.